HEGEMONI POLITIK PARTAI ISLAM DI PEMILU LEGISLATIF KOTA PADANGSDIDIMPUAN - Mudzakkir Khotib Siregar (Yurisprudentia: Jurnal Hukum Ekonomi, 2016)
Eights and electability legislative candidates and political parties is determined by the ability to use democracy, politikal realities and political ethics. The weight of the relationship to deteriorate and no lasting deterioration in the event of a third understanding of the relationship was well done jointly or one of the two components, namely a political party or political party and lagislative candidates. Popularity of policians and political parties in the 2009 legislative elections for city council Padangsidimpuan level, relatively no effect on electability.